Cellulase activity and dissolved organic carbon release from lignocellulose macrophyte-derived in four trophic conditions - Bottino, Flávia (Braz J Microbiol, 2016)
Considering the importance of lignocellulose macrophyte-derived for the energy flux in aquatic ecosystems and the nutrient concentrations as a function of force which influences the decomposition process, this study aims to relate the enzymatic activity and lignocellulose hydrolysis in different trophic statuses. Water samples and two macrophyte species were collected from the littoral zone of a subtropical Brazilian Reservoir. A lignocellulosic matrix was obtained using aqueous extraction of dried plant material (≈40 °C). Incubations for decomposition of the lignocellulosic matrix were prepared using lignocelluloses, inoculums and filtered water simulating different trophic statuses with the same N:P ratio. The particulate organic carbon and dissolved organic carbon (POC and DOC, respectively) were quantified, the cellulase enzymatic activity was measured by releasing reducing sugars and immobilized carbon was analyzed by filtration. During the cellulose degradation indicated by the cellulase activity, the dissolved organic carbon daily rate and enzyme activity increased. It was related to a fast hydrolysable fraction of cellulose that contributed to short-term carbon immobilization (ca. 10 days). After approximately 20 days, the dissolved organic carbon and enzyme activity were inversely correlated suggesting that the respiration of microorganisms was responsible for carbon mineralization. Cellulose was an important resource in low nutrient conditions (oligotrophic). However, the detritus quality played a major role in the lignocelluloses degradation (i.e., enzyme activity) and carbon release.